Dysregulation of Hepatitis B Virus Nucleocapsid Assembly in vitro by RNA-binding Small Ligands. Issue 10 (30th May 2022) - Patel, Nikesh; Abulwerdi, Fardokht; Fatehi, Farzad; Manfield, Iain W.; Le Grice, Stuart; Schneekloth Jr., John S.; Twarock, Reidun; Stockley, Peter G.
Graphical abstract: Highlights: Drug-like ligands bind a common motif in Hepatitis B Virus RNA Packaging Signals. Ligands dysregulate PS-mediated HBV nucleocapsid assembly in vitro at nanomolar concentrations. Assembly inhibitors may prevent formation of the PS RNA fold triggering assembly. Abstract: RNA sequences/motifs dispersed across the genome of Hepatitis B Virus regulate formation of nucleocapsid-like particles (NCPs) by core protein (Cp) in vitro, in an epsilon/polymerase-independent fashion. These multiple RNA Packaging Signals (PSs) can each form stem-loops encompassing a Cp-recognition motif, -RGAG-, in their loops. Drug-like molecules that bind the most important of these PS sites for NCP assembly regulation with nanomolar affinities, were identified by screening an immobilized ligand library with a fluorescently-labelled, RNA oligonucleotide encompassing this sequence. Sixty-six of these "hits", with affinities ranging from low nanomolar to high micromolar, were purchased as non-immobilized versions. Their affinities for PSs and effects on NCP assembly were determined in vitro by Surface Plasmon Resonance. High-affinity ligand binding is dependent on the presence of an -RGAG- motif within the loop of the PS, consistent with ligand cross-binding between PS sites. Simple structure–activity relationships show that it is also dependent on the presence of specific functional groups in these ligands. Some compounds are potent inhibitors of in vitro NCP assembly at nanomolar concentrations. Despite appropriate logP values, these ligands do not inhibit HBV replication in cell culture. However, modelling confirms the potential of using PS-binding ligands to target NCP assembly as a novel anti-viral strategy. This also allows for computational exploration of potential synergic effects between anti-viral ligands directed at distinct molecular targets in vivo . HBV PS-regulated assembly can be dysregulated by novel small molecule RNA-binding ligands opening a novel target for developing directly-acting anti-virals against this major pathogen.